Intradermal fractional-dose inactivated polio vaccine (fIPV) adjuvanted with double mutant Enterotoxigenic Escherichia coli heat labile toxin (dmLT) is well-tolerated and augments a systemic immune response to all three poliovirus serotypes in a randomized placebo-controlled trial. Issue 19 (26th April 2022) - Crothers, Jessica W.; Ross Colgate, Elizabeth; Cowan, Kelly J.; Dickson, Dorothy M.; Walsh, MaryClaire; Carmolli, Marya; Wright, Peter F.; Norton, Elizabeth B.; Kirkpatrick, Beth D.
Abstract: Eradication of poliomyelitis globally is constrained by fecal shedding of live polioviruses, both wild-type and vaccine-derived strains, into the environment. Although inactivated polio vaccines (IPV) effectively protect the recipient from clinical poliomyelitis, fecal shedding of live virus still occurs following infection with either wildtype or vaccine-derived strains of poliovirus. In the drive to eliminate the last cases of polio globally, improvements in both oral polio vaccines (OPV) (to prevent reversion to virulence) and injectable polio vaccines (to improve mucosal immunity and prevent viral shedding) are underway. The E. coli labile toxin with two or "double" attenuating mutations (dmLT) may boost immunologic responses to IPV, including at mucosal sites. We performed a double-blinded phase I controlled clinical trial to evaluate safety, tolerability, as well as systemic and mucosal immunogenicity of IPV adjuvanted with dmLT, given as a fractional (1/5th) dose intradermally (fIPV-dmLT). Twenty-nine volunteers with no past exposure to OPV were randomized to a single dose of fIPV-dmLT or fIPV alone. fIPV-dmLT was well tolerated, although three subjects had mild but persistent induration and hyperpigmentation at the injection site. A ≥ 4-fold rise in serotype-specific neutralizing antibody (SNA) titers to all three serotypes was seen in 84% of subjects receiving fIPV-dmLT vs. 50% of volunteers receiving IPV alone. SNA titers were higher in the dmLT-adjuvanted group, but only differences in serotype 1 were significant. Mucosal immune responses, as measured by polio serotype specific fecal IgA were minimal in both groups and differences were not seen. fIPV-dmLT may offer a benefit over IPV alone. Beyond NAB responses protecting the individual, studies demonstrating the ability of fIPV-dmLT to prevent viral shedding are necessary. Studies employing controlled human infection models, using monovalent OPV post-vaccine are ongoing. Studies specifically in children may also be necessary and additional biomarkers of mucosal immune responses in this population are needed. Clinicaltrials.gov Identifer: NCT03922061.